The Relationship Between Body Mass Index and Smoking History on the Incidence Rate of Hypertension in the Elderly at Rendeng Public Health Center - Detti Nur Irawati; Muhammad Azharul Hamdzi; Irma Kartikasari (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Hypertension in the elderly is a chronic disease that is resulted from various risk factors. The incidence of hypertension increases in the elderly, with a prevalence of 60-80% per year from the entire elderly population. A total of 1311 elderly who suffers from hypertension have a history of smoking and abnormal body mass index, so this research was conducted to determine how significant the risk of these two factors is.Objective: To analyze the relationship between body mass index and smoking history on the incidence of hypertension in the elderly in the Public Health Center of Rendeng.Methods: This research design was cross-sectional with a purposive sampling technique in elderly hypertensive patients in the Public Health Center of Rendeng by checking blood pressure and conducting interviews to fill out questionnaires. The data were analyzed by using the Spearman correlation test, and the test was strengthened using the C contingency correlation test.Results: This research used samples of 99 people. The results of the Spearman correlation test on body mass index obtained a significant value (p) of 0.001 (p<0.05), and a history of smoking obtained a significant value (p) of 0.330 (p>0.05).Conclusion: There was a relationship between body mass index and the incidence of hypertension in the elderly in the Public Health Center of Rendeng. However, there was no significant relationship that existed between smoking history.